Multimodal continuous turn-taking prediction using multiscale RNNs - Harte, Naomi (My University, 2018)
In human conversational interactions, turn-taking exchanges can be coordinated using cues from multiple modalities. To design spoken dialog systems that can conduct fluid interactions it is desirable to incorporate cues from separate modalities into turn-taking models. We propose that there is an appropriate temporal granularity at which modalities should be modeled. We design a multiscale RNN architecture to model modalities at separate timescales in a continuous manner. Our results show that modeling linguistic and acoustic features at separate temporal rates can be beneficial for turn-taking modeling. We also show that our approach can be used to incorporate gaze features into turn-taking models.
ICMI 2018 - 20th ACM International Conference on Multimodal Interaction
Keywords: Spoken dialog systems; Turn-taking modeling